Why We Fight: Nazi Strike - Capra, Frank (United States : Estree Hill Entertainment, 1943)
The second part of the acclaimed Frank Capra series "Why We Fight", "The Nazis Strike " (released in 1943), covers the rise of the Nazis to power as Hitler establishes his dictatorship over Germany and then has his armies march on Austria and Czechoslovakia before invading Poland and officially beginning the war. It emphasizes the failed attempts at appeasement meant to deter Hitler from his dreams of conquest. Capra documents how Hitler combined political maneuvers with military preparedness to position Germany for war. The section on the "Blitzkrieg" ("lighting war") attack on Poland is a detailed record of the fall of that nation before the German juggernaut. The subsequent film of the series, "Divide and Conquer," follows the German war machine as it continued to march across Europe. Like the entire series, "Nazy Strike" combine documentary facet with an explicit propagandistic overtone. Although they clearly do not provide a sophisticated, detailed and detached analysis of history, the "Why We Fight" series is a good place to look for the authentic film footage of the time, some of it quite rare, as well as for an excellent example of government-sponsored war propaganda.
Duration: 00:43:00
Keywords: Newsreels